Perbedaan Motivasi dan Keterampilan Belajar Peserta Didik Berprestasi Tinggi dan Rendah Serta Implikasi dalam Bimbingan dan Konseling - Edli, Haffizah; Mudjiran, Mudjiran (Konselor, 2015)
Motivation and learning skill are essential and mustbe owned by students to be successful in learning. But, the fact that are students with lack of learning motivation and learning skill. The aims from this research are: (1) to describing student’s learning motivation and learning skill which high achieving and underachieving, (2) to analyze student’s learning motivation and learning skill differences who high achieving and underachieving. This research using quantitative approach with comparative description type. This research conducted on students in VII and VIII grades at MTsN Salido Pesisir Selatan regency in 2013-2014 school year, with 258 students population, and 158 students as research sample using propotional random sampling techniques. Instrument for this research is questionnaire. Data analyzing for this research using descriptive statistic techniques and t-test using SPSS 16.00. Data analyzing revealed that (1) learning motivation students who is high achieving stand at high category, (2) learning motivation students who is underachieving stand at average category, (3) learning skill students who is high achieving stand at good category, (4) learning skill students who is underachieving stand at enough category, (5) there is a difference of learning motivation between students with high achieving and underachieving, (6) there is a difference of learning skill between students with high achieving and underachieving. The implication from this research to guidance and counseling is forming guidance counseling treatment programme that concern to students with underachieving in order to reach good learning result..